Preliminary studies of analgesic and anti-inflammatory properties of Caesalpinia ferrea crude extract - Carvalho, JCT; Teixeira, JRM; Souza, PJC; Bastos, J. K.; dosSantos, D.; Sarti, S. J. (Elsevier B.V., 1996)
The crude aqueous extract of the fruits of Caesalpinia ferrea Mart. (Leguminosae) has been investigated for possible anti-inflammatory and analgesic properties. The carrageenan induced rat hind paw edema was significantly inhibited (P < 0.05) by oral administration of 300 mg/kg of this extract. A centrally mediated analgesic effect was not observed, however, there was a dose dependent reduction in the number of total writhes induced by acetic acid.
Keywords: Caesalpinia ferrea; anti-inflammatory; analgesic; leguminosae